2020
DOI: 10.1101/2020.03.02.973347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

p38δ genetic ablation protects female mice from anthracycline cardiotoxicity

Abstract: BACKGROUND: The efficacy of an anthracycline antibiotic doxorubicin (DOX) as a chemotherapeutic agent is limited by dose-dependent cardiotoxicity. DOX is associated with activation of intracellular stress signaling pathways including p38 MAPKs. While previous studies have implicated p38 MAPK signaling in DOX-induced cardiac injury, the roles of the individual p38 isoforms, specifically, of the alternative isoforms p38 and p38, remain uncharacterized. OBJECTIVES: To determine the potential cardioprotective ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 46 publications
(39 reference statements)
0
14
1
Order By: Relevance
“…Currently, echocardiography is the method of choice in the clinical setting and ejection fraction is the preferred metric (Meijers & Moslehi, 2019; Perez et al, 2019). However, in our previous study, we demonstrated the role of preserved ejection fraction in some subjects as a potential cause of undiagnosed DOX‐induced cardiotoxicity (George et al, 2020). Electrocardiography (ECG) is another method to detect DOX cardiotoxicity in patients, however, this technique too has its limitations.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Currently, echocardiography is the method of choice in the clinical setting and ejection fraction is the preferred metric (Meijers & Moslehi, 2019; Perez et al, 2019). However, in our previous study, we demonstrated the role of preserved ejection fraction in some subjects as a potential cause of undiagnosed DOX‐induced cardiotoxicity (George et al, 2020). Electrocardiography (ECG) is another method to detect DOX cardiotoxicity in patients, however, this technique too has its limitations.…”
Section: Introductionmentioning
confidence: 75%
“…Beyond 2 min, mice became stressed and motion artifacts were introduced into the signals. Mice were then anesthetized using isoflurane (1–2.5%, 1 ml/min oxygen) using an EZ anesthesia machine to maintain a heart rate of ~400 bpm (for echocardiography simultaneously performed and previously published (George et al, 2020)). Once unconscious, mice were transferred to the mouse platform of a Vevo 3100 ultrasound machine (FUJIFILM VisualSonics) and anesthesia administration was continued via a nose cone.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations